Cold Water System Design In Low-Rise Office Building Using Revit - yasni, hidayati; M Amin, Sri Yulis (Research Progress in Mechanical and Manufacturing Engineering, 2022)
A study about a cold-water system specially for low rise building has been aim for this research work. Most of cold-water system provide water throughout the building, the purpose of which is to provide enough water for the living inside especially during the peak hour. There are two basic systems of cold-water system used in domestic dwelling which are direct cold-water system and indirect water system. Referring to Uniform Building by Laws (UBBL) and Commission of Malaysian Water Services (SPAN) as standard requirement for Malaysia is one of the references to explain and predict new building model. Building Information Modelling (BIM) Autodesk Revit is the software used to design the cold-water system in a new building. As a result, the creation of new buildings equipped with cold water systems that meet authorities' standards has been explored and a system for a peak consumption have been built.